Empresas madeireiras com certificação florestal e marketing verde: estratégias comunicacionais do grupo Cikel - PIMENTA, Ana Carolina (2008)
In the nineties, the politics of forest administration in Brazil started to be determined by the hegemonic speech of the sustainable development. Pressed by environmentalists and other social agents, the companies are guided, through market influences, to reduce the predatory actions to the environment. With that, non-governmental organizations (NGOs) joined the forest industry for the development of an outline of a forestry certification known as the Forest Stewardship Council - FSC, which is destined to improve the forest practices all over the world. In this context, companies with certified areas start to praise the differentiated aspect of its activities, adopting the green marketing as communicational strategy in the search of constructing "a sustainable" image, and in parallel, for new market choices. This work intends to analyze the communication process in companies which adopt practices of Maintainable Forest Handling (MFH) in the Amazonian. Using a case study, we analyze the performance of Cikel Brasil Verde Madeira LTD., which is a company recognized as a true example to be followed. We thought it was pertinent to analyze some of the effective operations, investigate the ideological elaborations about the speech it is possible to preserve, producing. The choice for the Cikel Group is because it is the largest and oldest timber company operating in Amazonia, and because it is one of the pioneers in Brazil to have its forests certified by the FSC. Aided by the theoretical-methodological framework of the Analysis of the Speech, this work searches for understand the formulated and spread speech by the Cikel Group, delineating its institutional identity. In the materialized interdiscursive of the statements, it is possible to identify how the different acting subjects are positioned and how they link the political, economical and ideological components that institute and maintain the institutional partnerships of the company. In conclusion, we made a critical reflection around the common vision which says that the forest certification would be the most legitimate form to get a sustainable use of the forest, what reveals the social aspect weakness in politics of FSC and companies as Cikel.